MECKEL-GRUBER SYNDROME - A CASE REPORT - S., Naveen N.; K., Vishal; V., Vinay K. (Journal of Health and Allied Sciences NU, 2013)
Meckel Gruber syndrome (MGS) is a rare lethal autosomal recessive disorder. It is characterized by triad of features having occipital meningoencephalocoele, polycystic kidneys and post-axial polydactyly. We report a rare case of MGS which was diagnosed by antenatal ultrasound examination and confirmed later when aborted at 21 weeks of gestation.
Keywords: Meningoencephalocoele; Polydactyly; Polycystic kidney